Optimization of the technological mode of processing of Karatau phosphorites on cyclic technology by method of mathematical planning of an experiment - S. O. Akhmetova (Алматы технологиялық университетінің хабаршысы, 2021)
In the article the results of studies of decomposition process of Karatau phosphorites by phosphoric acid are presented. Mathematical processing of the results of an experiment was carried out. Kinetic characteristics of the chemical reaction are determined, which can be used to evaluate technological parameters and select optimal conditions of phosphorite decomposition. The process of decomposition of phosphorites of different structure was optimized by the method of mathematical planning of the experiment. The obtained dependencies can be used for determination of decomposition parameters under production conditions in order to achieve the maximum process indicators.